2012
DOI: 10.4081/rt.2012.e47
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol granuloma of the anterior mediastinum with osseous metaplasia

Abstract: Cholesterol granuloma is a well-characterized entity comprised of a foreign-body giant cell-reaction that forms in response to the presence of cholesterol crystals. It is usually found in the middle-ear or mastoid process in patients with diseases associated with chronic inflammation such as cholesteatoma and otitis media. They are rarely seen in the mediastinum. Osseous metaplasia is an exceedingly rare feature of cholesterol granulomas only reported twice in the literature. We report a case of a cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Over the last 10 years, four single case reports of an unusual lesion in the anterior mediastinal compartment have been described under the designation of cholesterol granuloma [2][3][4][5]. The first description of such a case is credited to Luckraz et al [2] who described this unusual lesion in a 74-year-old man who underwent cardiac evaluation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Over the last 10 years, four single case reports of an unusual lesion in the anterior mediastinal compartment have been described under the designation of cholesterol granuloma [2][3][4][5]. The first description of such a case is credited to Luckraz et al [2] who described this unusual lesion in a 74-year-old man who underwent cardiac evaluation.…”
Section: Discussionmentioning
confidence: 93%
“…Histologically, all three cases shared very similar histological features. In addition to these cases, Ezzat and Alowami [5] described a 75-year-old man with history of angina, hypertension, and peripheral vascular disease who was found to harbor a similar lesion. However, contrary to the cases previously published, this particular case was histologically slightly different as the lesion also showed prominent foci of osseous metaplasia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In their review of the literature, they have only found four single case reports. [2][3][4][5] These eight previously reported cases occurred in 58-to 75-year-old male patients. Our two patients were also male.…”
Section: Letter To the Editormentioning
confidence: 95%
“…Only one previously reported case was said to be found in thymic remnant but without illustration. 5 Other cases were only described as located in the region of the thymus, 1 behind the manubrium, 2 adherent to the thymus, 3 or overlying the innominate vein. 4 In conclusion, rarely reported pseudo-tumorous lipid granulomas of the thymus deserve to be better known as possible lucky incidental findings in patients with suspected thymoma.…”
Section: Letter To the Editormentioning
confidence: 99%